Policies and Instruments for Self-Enforcing Treaties - Bård Harstad; Francesco Lancia; Alessia Russo (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We characterize the optimal policy and policy instruments for self-enforcing treaties when countries invest in green technology before they pollute. If the discount factor is too small to support the first best, then both emissions and investments will be larger than in the first best, when technology is expensive. When technology is inexpensive, countries must instead limit or tax green investment in order to make future punishment credible. We also uncover a novel advantage of price regulation over quantity regulation, namely that when regulation is sufficiently flexible to permit firms to react to non-compliance in another country, the temptation to defect is reduced. The model is tractable and allows for multiple extensions.
Keywords: D86; F53; H87; Q54; 330; climate change; environmental agreements; green technology; policy instruments; repeated games; compliance; self-enforcing treaties